Factors Influencing the Willingness of Universities’ Business Management Departments to Implement Online Entrepreneurship Program and Its Effectiveness - Wang, Yu-Min; Chiou, Chei-Chang (Frontiers in Psychology, 2020)
With the steady increase and popularization of innovations and applications on the Internet, more and more people are searching for and purchasing products online. The boom in e-commerce stimulates opportunities in online entrepreneurship. However, the risks and failure rate for online entrepreneurship are relatively high. Therefore, some universities are standardizing the implementation of online entrepreneurship programs (OEP) with the aim of equipping students with knowledge for online entrepreneurship through instruction and practical methods to increase the chance of successful online entrepreneurship and also enhance the professional image of the department. The main purpose of the present study is to explore the key influencing factors affecting the willingness of universities' department of business administration to implement OEP and its effectiveness. Using the technology-organization-environment (TOE) framework by Tornatzky and Fleischer (1990), the Innovation Diffusion Theory (IDT) by Rogers (1983), and the OEP characteristics as the foundation, the present study developed a model to analyze and elucidate the key factors for OEP implementation willingness and OEP effectiveness. Survey data were collected from teachers at universities' business management departments, and structural equation modeling (smartPLS) was utilized to verify the research model and hypothesis. The present study found integrating the TOE framework and the IDT can be used to analyze the key factors influencing OEP implementation willingness and its effectiveness at universities' business management departments. When implementing the implementation of OEP, business management departments at universities need to take into account factors from three contexts: innovation, organization, and environment. Innovative factors greatly influence the willingness of departments to implement OEP, but organizational and environmental factors have a greater influence on the effectiveness of OEP implementation. The results of the present study will enable academia and education practitioners to better understand how to implement OEP and achieve results in the context of business education at universities.